The desert and misery: Indians and taxation in southern Peru (Sibaya, 1822) - Díaz, Alberto (2006)
This article attempts discusses the local context associated with taxes and tributes in the Andean communities of the Peruvian South, particularly in the community of Sibaya. Documents desribing the social and economic conditions in which Sibaya inhabitants lived are analyzed in connection with two issues: (1) the problem that tax collection represented for foreign authorities (sub-delegates) and, (2) the impossibility of the community of Sibaya to pay taxes and tributes due to the death of community members, the territorial dispersion of the local and foreign inhabitants, and the precarious condition of the lands. This is an article which is partly aimed at offering a testimony on a moment in the past of the Andean societies located in Tarapaque during the 19th century and is ,therefore, an opportunity to go through the silent period of  Peruvian history to which the people living in the area of the Atacama Desert adhered.